2002
DOI: 10.1007/s00125-002-0869-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects on heart rate variability of metoprolol supplementary to ongoing ACE-inhibitor treatment in Type I diabetic patients with abnormal albuminuria

Abstract: difference in heart rate between inspiration and expiration; LF, square root of power of the low frequency oscillation; LF power, power of the low frequency oscillation; Mean RR, mean of all normal RR intervals; Mean RR D-N, difference between awake and sleep time in mean RR; RSA, respiratory sinus arrhythmia; SDANN, standard deviation of the mean RR in all 5 min segments in a 24 h period; SDNN, standard deviation of all normal RR intervals; SDNN index, mean of SD's calculated on 5 min of RR intervals during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 66 publications
1
23
1
2
Order By: Relevance
“…In experimental and in spontaneous nocturnal hypoglycaemia, prolongation in QTc has been demonstrated [32,33], and pre-treatment with a beta blocker demonstrably prevented abnormal repolarisation during experimental hypoglycaemia [32]. We have previously shown that it is possible to improve heart rate variability parameters by B1-selective beta blockade [19]. This study now shows that it is also possible to reduce the QTc interval by B1-selective beta blockade.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In experimental and in spontaneous nocturnal hypoglycaemia, prolongation in QTc has been demonstrated [32,33], and pre-treatment with a beta blocker demonstrably prevented abnormal repolarisation during experimental hypoglycaemia [32]. We have previously shown that it is possible to improve heart rate variability parameters by B1-selective beta blockade [19]. This study now shows that it is also possible to reduce the QTc interval by B1-selective beta blockade.…”
Section: Discussionmentioning
confidence: 51%
“…The supplementary beta blocker treatment caused no change in systolic AMBP (daytime run-in 134±11 mm Hg, daytime placebo 135±12 mm Hg, daytime metoprolol 133± 10 mm Hg, p=NS) but did cause a decrease in daytime diastolic AMBP (daytime run-in 82±9 mm Hg, daytime placebo 83±8 mm Hg, daytime metoprolol 80±8 mm Hg, p=0.04) and an improvement in HRV parameters reflecting parasympathetic modulation (for details, see [19]). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic dysfunction also correlates with higher-range normoalbuminuria in patients with type 1 diabetes, suggesting a possible role for SNS activation in the transition from normo-to microalbuminuria (39) and activation of intrarenal RAAS, intraglomerular hypertension, and hyperfiltration in animals and in humans with type 1 diabetes (40)(41)(42). Therapeutic interventions using pharmacologic SNS blockade in type 1 diabetes resulted in lower BP and improved HRV (43). Meanwhile, in streptozotocin-induced diabetic rats, renal hyperfiltration can be prevented with sympathetic renal denervation (40).…”
Section: Discussionmentioning
confidence: 97%
“…Theoretically, adding a central sympatholytic agent to ACE inhibition therapy could maximize the beneficial effects of ACE inhibition. In this regard, Ebbehoj et al (8) have shown that adding ␤-blocker treatment to concurrent ACE inhibition in patients with Type I diabetes improved autonomic function. Fig.…”
Section: Perspectivesmentioning
confidence: 99%